2020
DOI: 10.1101/2020.06.13.150037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein citrullination was introduced into animals by horizontal gene transfer from cyanobacteria

Abstract: Protein post-translational modifications (PTMs) add an enormous amount of sophistication to biological systems but their origins are largely unexplored. Citrullination, a key regulatory mechanism in human physiology and pathophysiology, is particularly enigmatic in an evolutionary context. The citrullinating enzymes peptidylarginine deiminases (PADIs) are ubiquitous across vertebrates but absent from yeast, worms and flies. Here, we map the surprising evolutionary trajectory of PADIs into the animal lineage. W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 138 publications
(193 reference statements)
1
1
0
Order By: Relevance
“…The lack of PAD orthologs in Echinoderms indicates that the transfer occurred after the major radiation events within the Deuterostoma and could explain the uniqueness of PADs in the chordate lineage. Furthermore, it has been shown that cyanobacteria PAD can actively citrullinate/deiminate mammalian proteins in a calcium-dependent manner [ 150 ], and this is in a similar vein as our suggestion here, based on the findings of our current study, that sea urchin proteins may be deiminated by cyanobacteria, or possibly other microbiota, PAD/ADI. The modulation of sea urchin immunity, metabolism, and gene regulation via deimination by PAD/ADI of microbiota could point to novel mechanisms in the regulation of key pathways in echinoderm biology.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of PAD orthologs in Echinoderms indicates that the transfer occurred after the major radiation events within the Deuterostoma and could explain the uniqueness of PADs in the chordate lineage. Furthermore, it has been shown that cyanobacteria PAD can actively citrullinate/deiminate mammalian proteins in a calcium-dependent manner [ 150 ], and this is in a similar vein as our suggestion here, based on the findings of our current study, that sea urchin proteins may be deiminated by cyanobacteria, or possibly other microbiota, PAD/ADI. The modulation of sea urchin immunity, metabolism, and gene regulation via deimination by PAD/ADI of microbiota could point to novel mechanisms in the regulation of key pathways in echinoderm biology.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies indicate the emergence of PADs within the chordates via horizontal gene transfer from cyanobacteria [ 150 ]. The lack of PAD orthologs in Echinoderms indicates that the transfer occurred after the major radiation events within the Deuterostoma and could explain the uniqueness of PADs in the chordate lineage.…”
Section: Discussionmentioning
confidence: 99%